Rola opinii konsumentów w formułowaniu celów rozwoju turystyki obszaru recepcji ruchu turystycznego - Rapacz, Andrzej; Jaremen, Daria E. (The Role of Consumers' Opinion in Defining Tourism Development Objectives for the Area of Tourist Movement Reception, 2005)
In the process of elaborating tourism development objectives for the areas of tourist movement reception, the first position is taken by activities resulting in defining objectives of such development. One of the conditions for describing the targets in a proper way is to conduct and take advantage of market research as the basis for such work. Among others, direct research conducted by means of personal contact with tourists seems very useful. The hereby article presents the concept of such research, which was taken up in the process of preparing development strategy and tourism promotion for the town of Zgorzelec and the surrounding areas, as well as their results. They became the basis for creating operational programs and tasks resulting from them in the field of shaping tourist offer for Zgorzelec and promoting its distribution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1067, s. 122-129